La analogía del "esse" en el tomismo intensivo de Cornelio Fabro y Bernhard Lakebrink = Abweichender Titel: The analogy of "esse" in the Intensive Thomism of Cornelio Fabro and Bernhard Lakebrink - Rubio Hípola, Ignacio María (Cauriensia, 2025)
Cornelio Fabro and Bernhard Lakebrink stood out in the 20th century as two of the most prominent philosophers who made an effort to recover and update the doctrine of Thomas Aquinas in dialogue with some of the main authors of the idealist (such as Hegel), phenomenological (such as Husserl or Heidegger) or existentialist (like Kierkegaard) tradition. In this article we intend to highlight their fundamental similarities in their metaphysical proposal, particularly on the topic of the analogy of "esse", as well as show the main differences between them. To do this, after an introduction that provides the proper context, we will proceed to analyze the individual proposals of each one to establish the appropriate comparisons in the conclusions.